CHARACTERISTICS OF AFRICAN POLITICAL LEADERS: PERSPECTIVES OF AFRICAN INTERNATIONAL STUDENTS - Emynorane, Ralaivao Hanginiaina; Arrive, Jean Tsitaire (Journal of Governance and Public Administration, 2024)
This study aims to explore the characteristics of political leaders in Africa through the perspectives of international students originating from the continent. The characteristics of political leadership in Africa are often influenced by complex historical, social and economic contexts. In this study, the authors use a qualitative approach with interviews and surveys to collect data from international students from various countries in Africa. The main aim of this study is to understand how students view the characteristics of political leaders in their home countries, including attributes such as charisma, communication skills, accountability mechanisms, transparency and good governance. This study also examines how these perceptions can help shape a broader understanding of political leadership in Africa, as well as the challenges and opportunities faced by political leaders in the region. It is hoped that the findings from this research will contribute to the development of political leadership theory in Africa and provide deeper insight into political dynamics on the continent.